2017
DOI: 10.18632/oncotarget.22493
|View full text |Cite|
|
Sign up to set email alerts
|

A new bioluminescent reporter system to study the biodistribution of systematically injected tumor-derived bioluminescent extracellular vesicles in mice

Abstract: In vivo biodistribution and fate of extracellular vesicles (EVs) are still largely unknown and require reliable in vivo tracking techniques. In this study, in vivo bioluminescence imaging (BLI) using Renilla luciferase (Rluc) was developed and applied to monitoring of EVs derived from thyroid cancer (CAL-62 cells) and breast cancer (MDA-MB-231) in nude mice after intravenous administration and was compared with a dye-based labeling method for EV derived from CAL-62 cells. The EVs were successfully labeled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 80 publications
3
103
0
1
Order By: Relevance
“…On the other hand, genetically labeled exosomes have an advantage in comparing their in vivo distribution with and without additional labeling. Especially, genetically labeled exosomes can be utilized to monitor the effects of surface modifications, such as covalent binding or membrane integration, which may cause structural or functional changes in the membranes of exosomes [67]. [74,76] Labeling of exosomes by encapsulation has been performed with various labeling probes such as radioisotopes, nanoparticles, and fluorescent dyes ( Table 4).…”
Section: Labeling Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, genetically labeled exosomes have an advantage in comparing their in vivo distribution with and without additional labeling. Especially, genetically labeled exosomes can be utilized to monitor the effects of surface modifications, such as covalent binding or membrane integration, which may cause structural or functional changes in the membranes of exosomes [67]. [74,76] Labeling of exosomes by encapsulation has been performed with various labeling probes such as radioisotopes, nanoparticles, and fluorescent dyes ( Table 4).…”
Section: Labeling Methodsmentioning
confidence: 99%
“…Another study performed without covalent binding suggested that labeling exosomes with lipophilic dyes also slightly changes the biodistribution of exosomes. The researchers labeled exosomes containing luciferase, with a lipophilic fluorescent dye and compared the biodistribution of the exosomes with and without the lipophilic dyes [67]. The exosomes without the lipophilic dye, accumulated in the organs in the following order: lung > liver > spleen > kidney.…”
Section: Covalent Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that EVs have intrinsic cell targeting properties: cell surface structures, such as tetraspanins and integrins, may direct the EV uptake towards specific cells and protect therapeutic agents from opsonization and recognition by phagocytes, leading to a longer half-life and reduced side-effects in healthy cells and tissues [42,43]. EVs have been shown to be safe in several clinical trials [44,45], while their effectiveness in cancer therapy may strongly depends on their ability of EVs to target the tumor tissue: however, despite intense research in the field, still little is known about their in vivo biodistribution [35,[46][47][48][49].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Western blotting was carried out as previously described. 15 Cell or EV lysates were prepared in lysate RIPA buffer (Thermo Fisher Scientific), to which a cocktail of protease inhibitor was added (Sigma-Aldrich Co., St Louis, MO, USA). An equal amount of protein was loaded and run on a 10% SDS-PAGE gel.…”
Section: Western Blottingmentioning
confidence: 99%